Translanguaging in Indonesian Corporate Setting: Sociolinguistic Phenomenon, Affordances, and Constraints - Saraswati, Nais (ELTALL: English Language Teaching, Applied Linguistic and Literature, 2025)
In Indonesia’s increasingly globalized and multilingual corporate landscape, translanguaging—the fluid use of multiple languages in communication—has emerged as a prevalent and strategic practice. This paper explores Indonesian-English translanguaging in corporate settings as a sociolinguistic phenomenon, as it socially situated, interaction-based, identity-linked, power-sensitive, context-dependent, and meaning-oriented. Using a library-based interpretivist approach, the research illustrates how employees employ translanguaging to clarify complex ideas, embed cultural relevance, and facilitate real-time collaboration. However, persistent constraints remain, such as language hierarchies, unequal English proficiency, and institutional resistance. The findings advocate for a reframing of translanguaging—not as linguistic deviation, but as a valuable communicative resource that bridges cultural divides, boosts workplace productivity, and supports professional advancement.